Rozkłady a-stabilne w ewolucyjnych algorytmachglobalnej optymalizacji parametrycznej - Prętki, Przemysław
The aim of this dissertation is to give an account on theroetical aspects of stabIe distributions and their practical application to modem stochastic global optimization algorithms. Particular emphasis is placed on special charateristics of stable family which have an effect on effectiveness of evolutionary algorithms. The c1ass of stable distributions is unique, esspeccialy against commonly used Gaussian model, from many reasons, e.g.: generally they variance is infmite while an expectation value exists only for some particular cases. In the light of these distinctive features the so-called sourounding and symmetry effect is discussed in more detail. 80th mentioned phenomena are to a large extend responsable for dec1ine in effectivness global optimization procedures that are based on Gaussian mutation.
Keywords: optymalizacja globalna; rozkłady stabilne; systemy wykrywania uszkodzeń; algorytmy ewolucyjne, systemy wykrywania uszkodzeń